Legal Certainty of Written Evidence of Land Formerly Owned by Indigenous Communities in Land Registration in Indonesia - Timoty Ezra Simanjuntak; Jokki Obi Mesa Situmeang; Aldo Prasetyo Riyadi; Mohammad Didi Ardiansah; Andi Sitti Ainy Nur Alifah (Dinasti Research, 2025)
This research aims to examine the legal certainty regarding written evidence of land formerly owned by indigenous communities in the context of land registration in Indonesia following the enactment of Government Regulation No. 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration. Additionally, this research explores the mechanisms for resolving land ownership disputes based on written evidence of land formerly owned by indigenous communities. The research methodology is conducted through a normative juridical approach, supplemented by interviews with key informants and an analysis of relevant legislation. The findings indicate that, according to Government Regulation No. 18 of 2021, written evidence of land formerly owned by indigenous communities is deemed invalid and serves only as a clue for land registration in Indonesia. Consequently, there has been a shift in the evidentiary power that was previously recognized as valid evidence; under the new regulation, it is now merely a clue for land registration. Nevertheless, in the event of a dispute over ownership of such land, written evidence of land formerly owned by indigenous communities may still be utilized as evidence in court.